Foreign Language Learners' Anxiety in Language Skills Learning: A Case study at Universitas Kristen Indonesia - Male, Hendrikus (JET (Journal of English Teaching), 2018)
Anxiety has been a matter of substantial concern in foreign language (FL) learning setting for educators since it is a major obstacle learners need to overcome (Ellis, 2008; Wu, 2010).This study was aimed at finding out students’ language anxiety in learning the four language skills at a university level in English as a FL context. The participants were 71 students of the English education Department of Universitas Kristen Indonesia. Data was collected by administering a set of questionnaire. To support the data, interview was conducted to some of the respondents. Findings showed that the majority of the students were more anxious on writing skill, followed by reading, speaking and listening in their language learning process. It is highly recommended that the teachers or faculties be more creative in making the language skills classes atmosphere more fun and relaxing so that the students could achieve higher learning results. Keywords: anxiety, non-native learners, language learning process